First american records of Aphis intybi (Hemiptera: Aphididae) with notes on two other related adventive species in Argentina - Mier Durante, Milagros Pilar; Foottit, Robert; Dohlen, Carol D. Von; Ortego, Jaime (Florida Entomological Society, 2019)
Aphis intybi Koch is recorded for the first time in North and South America. Measurements for the identification of this species in comparison with Aphis craccivora Koch are given. Aphis cytisorum Hartig is recorded for the third time in Argentina. Data on morphological variation, geographical distribution, and host plants of these species in Argentina are provided. Their morphological identification is supported by comparison of DNA sequences of the mitochondrial cytochrome oxidase subunit 1 (DNA barcode) and subunit 2.